KREATIVITAS DWIYASMONO DALAM KARYA TARI HARJUNA KERATARUPA - Fitri Monika Sari; Nanik Sri Prihatini (Institut Seni Indonesia Surakarta, 2019)
This research focuses on Dwiyasmono’s creativity in creating Harjuna–Keratarupo Dance. Harjuna–Keratarupo Dance is a phetilan dance two adult males. Issues raised in the research is about the form of Harjuna–Keratarupo Dance. And about Dwiyasmono’s creativity in the Creations of Harjuna–Keratarupo Dance. This research is a Qualitative research using descriptive methods of analysis and the technical collection of observations, interviews, bibliography studies and Documents. To analyse the shape of the dish using form concepts expressed by Suzane K. Langer and its elements the constituent was outlined using Soedarsono’s theory. To Explain Dwiyasmono’s creativity analyzed using theory Rhodes that creativity there are four elements, namely person, press, process, product. The results of the research known as Harjuna-Keratarupo Dance in the form of a divided into three parts, namely the Maju Beksan, Beksan and Mundur Beksan. This dance has the merging of two styles of dance motion. Dwiyasmono’s creativity in the cupping section of the Surakarta movement is combined with the movement of Yogyakarta style. The dance music in the dance is colored with a leather puppet pack. The development of the garage is influenced by external factors and internal factors, especially for its withdrawal.Keywords: Harjuna Keratarupo, form, Dwiyasmono, creativity.